Ultrasound-Guided Regional Anesthesia for Clavicle Fixation in a Pregnant Patient with Traumatic Brain Injury: A Case Report and Pathophysiological Review - Koko Agung Tri Wibowo; Aura Ihsaniar; Husni Thamrin (HM Publisher, 2025)
The anesthetic management of a third-trimester pregnant patient with a concurrent traumatic brain injury (TBI) and a surgical fracture presents a profound clinical dilemma. The conflicting demands of maternal neuroprotection, fetal stability, and surgical anesthesia necessitate a carefully considered approach, as standard general anesthesia carries significant risks for both mother and fetus. A 25-year-old female at 28 weeks’ gestation presented after a motor vehicle accident with a displaced right clavicle fracture and a TBI characterized by a clinically mild presentation (Glasgow Coma Scale 14) and a radiologically significant acute subdural hemorrhage. To provide surgical anesthesia for open reduction and internal fixation while circumventing the risks of general anesthesia, a primary regional anesthetic was performed. An ultrasound-guided single-shot interscalene brachial plexus block, supplemented with a superficial cervical plexus block, provided dense surgical anesthesia. This technique ensured remarkable maternal hemodynamic stability, maintained a reassuring Category I fetal heart tracing throughout, and completely avoided intraoperative systemic opioids and sedatives. The postoperative course was notable for excellent, opioid-sparing analgesia and an uncomplicated recovery for both mother and infant. In conclusion, this case provides an illustrative example of how a meticulously executed regional anesthetic technique can serve as a primary and potentially superior modality in this high-risk patient population. It successfully navigated the competing pathophysiological demands, suggesting that regional anesthesia should be a first-line consideration in select, complex trauma scenarios involving pregnancy and TBI.